Owen and the soldier - Thompson, Lisa Joann (Edinburgh: Barrington Stoke, 2019)
A crumbling stone soldier sits on a bench in the park. Only Owen understands how important he is. At home, Owen and his mum are struggling and there's nobody he can talk to. Hidden away in the park, Owen feels free to be himself. When the war-weary soldier is listening, his worries slip away. But nobody else cares about the soldier, and the town council want to tear him down. Owen's the only one who can save him but can he find the courage to speak up before it's too late? A touching story of loss and remembrance from Lisa Thompson, the award-winning author of The Goldfish Boy. Particularly suitable for struggling, reluctant or dyslexic readers aged 8+
Keywords: Children's stories